Melioidosis of the Head and Neck: A Case Series from Eastern India - Srujana Mohanty; Saurav Sarkar; Baijayantimala Mishra (MDPI AG, 2020)
Melioidosis is an emerging entity in India. Though it is a potentially fatal disease, prognosis is excellent with early detection and appropriate management, especially of localized infections like abscesses of the head and neck area. We report nine cases of focal abscesses in the head and neck region due to Burkholderia pseudomallei, the causative agent of melioidosis, presenting to our hospital within a span of two-and-half years. Since melioidotic abscesses in the cervicofacial and head and neck region are likely to be confused with cold abscesses caused by Mycobacterium tuberculosis in a tuberculosis-endemic country like India, increased vigilance is necessary because of the widely divergent treatment modalities of the two disease entities.